Brain abscess caused by Nocardia asiatica - Uneda, Atsuhito (Surg Neurol Int, 2016)
BACKGROUND: Nocardia infection of the central nervous system leading to brain abscess is a rare condition but has a high mortality rate. Among the species of Nocardia, only three cases of brain abscess due to Nocardia asiatica infection have been reported. CASE DESCRIPTION: A 65-year-old man with a history of autoimmune hemolytic anemia treated with prednisolone presented to our hospital because of occipital headache. Brain magnetic resonance imaging showed bilateral occipital lesions. The patient underwent craniotomy and resection of the left occipital lobe lesion. N. asiatica was identified by 16S rRNA sequencing of the resected specimen. Treatment with trimethoprim/sulfamethoxazole led to a complete resolution of the brain lesion. CONCLUSION: Because of the different antimicrobial sensitivity patterns among Nocardia species, both appropriate subtyping and susceptibility testing of uncommon species such as N. asiatica are required for the successful treatment of nocardial infections.